Dye Wastewater Treatment Using Self-made Nd doped Ti/SnO2-Sb Electro-Catalytic Electrodes - Li, Shanping; Lian, Junfeng; Wang, Hongbo; Cui, Jiangjie; Li, Chong (Asian Journal of Chemistry, 2011)
Neodymium was selected as a promoter for Ti/SnO2-Sb electrode to enhance its electro-catalytic characteristics and Nd doped Ti/SnO2-Sb electrodes were prepared by immersion method. The optimum conditions for Nd-doped Ti/SnO2-Sb anode preparation were proved to be 1 mol % Nd/Sn and 550 ºC as an annealing temperature. The prepared electrodes were characterized by scanning electron microscopy, electron dispersive spectrometry, X-ray diffraction and X-ray photon-electron spectroscopy. It was suggested that the introduction of Nd atoms into the surface coating of the electrode can increase the surface area, the number of active site and the proportion of lattice oxygen, thus increase the electro-catalytic ability of the Ti/SnO2-Sb electrode. X-Ray photoelectron spectroscopy (XPS) analysis showed that the oxidation state of Sn, Sb and Nd were +4, +5and +3, respectively and the probable forms are SnO2, Sb2O5 and Nd2O3. The cyclic voltammetry and service life test showed that the Nd doped Ti/SnO2-Sb electrode had higher oxygen evolution potential and performed a longer service life. The increase of the biodegradability of reactive brilliant red X-3B wastewater indicated that the prepared Nd-doped Ti/SnO2-Sb electrode can be used in the pre-treatment of biological treatment.